2018
DOI: 10.3892/ol.2018.8239
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-192 inhibits the proliferation, migration and invasion of osteosarcoma cells and promotes apoptosis by targeting matrix metalloproteinase-11

Abstract: MicroRNAs (miRNAs) are small non-coding RNAs that regulate gene expression during stem cell growth, proliferation and differentiation. miRNAs are also involved in the development and progression of a number of cancer types, including osteosarcoma (OS). miR-192 is significantly downregulated in various tumors, including lung, bladder and rectal cancer. miR-192 expression is associated with the migration and invasion of OS cells. However, the expression of miR-192 and its effects on the development of OS have no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Growing evidence has revealed that miRNAs are involved in human diseases such as cancer, diabetes, hypertension, and cardiovascular disease [24]. Since a single miRNA can target several mRNAs, and being components of a larger regulatory network [25], miRNAs can affect cellular function, differentiation, proliferation, and apoptosis, as well as tumor formation, metastasis and drug resistance in carcinogenesis [26,27]. Here, we established and validated a 3-miRNA-based classifier to increase the accuracy of predicting the prognosis of patients with OS.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence has revealed that miRNAs are involved in human diseases such as cancer, diabetes, hypertension, and cardiovascular disease [24]. Since a single miRNA can target several mRNAs, and being components of a larger regulatory network [25], miRNAs can affect cellular function, differentiation, proliferation, and apoptosis, as well as tumor formation, metastasis and drug resistance in carcinogenesis [26,27]. Here, we established and validated a 3-miRNA-based classifier to increase the accuracy of predicting the prognosis of patients with OS.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the results of another study demonstrated that both the expression of miRNA-192-3p and miRNA-192-5p were decreased in stage IIIB colon cancer as compared to healthy tissues (32). The reduction in the expression level of this tumor suppressor miRNA has been reported in osteosarcoma, lung cancer and pancreatic cancer, where it has been reported that miR-192 exhibits a tight association with the regulation of cell proliferation and apoptosis (33)(34). Moreover, it has been reported that the downregulation of miR-192 in hepatocellular carcinoma (HCC) may provide a signal that upregulates SLC39A6/SNAIL, a molecule involved in cell invasion, which in turn deteriorates patient outcome (35).…”
Section: Discussionmentioning
confidence: 71%
“…Besides, a series of studies reported that miRNA‐192 and miRNA‐215 have been identified as a tumor suppressor in osteosarcoma (Shang et al, 2018), colon cancer (Vychytilova‐Faltejskova et al, 2017), epithelial ovarian (Lin, Jin, Xu, Zhou, & Cui, 2017), and whereas it may act as an oncogene in hepatocellular carcinoma (Yan‐Chun et al, 2017), endometrial cancer (Gao, Cai, & An, 2018), and GC (Jin et al, 2011; Xu & Fan, 2015; X. Zhang et al, 2018a, 2018b). miRNA‐192 may function as a tumor suppressor in osteosarcoma cells (OS), and capable of inhibiting the proliferation, migration, and invasion of OS and promotes apoptosis by targeting matrix metalloproteinase‐11 (Shang et al, 2018). However, a study demonstrates that miRNA‐192‐5p can promote the proliferation and metastasis of hepatocellular carcinoma cell by targeting SEMA3A (Yan‐Chun et al, 2017).…”
Section: Discussionmentioning
confidence: 99%